Whole Class or Small Group Fluency Instruction: A Tutorial of Four Effective Approaches - Melanie R. Kuhn (MDPI AG, 2020)
Four scientifically validated approaches to fluency instruction (Fluency-Oriented Reading Instruction, Wide Fluency-Oriented Reading Instruction, Fluency-Oriented Oral Reading, and Wide Fluency-Oriented Oral Reading) are reviewed. Two for the whole class and two for small groups. Key components of fluency, automaticity, and prosody are defined, and their contribution to reading comprehension is discussed. Automaticity contributes through its freeing up of attention to attend to meaning, and prosody contributes through its addressing of pacing and expression that, in turn, reflect textual meaning. Four principles for effective fluency instruction are also presented: Modeling, extensive opportunities for practice, the use of scaffolding, and the incorporation of prosodic elements. The four instructional approaches presented in this article are based on two different strategies for integrating extensive opportunities to read: Repeated versus wide reading. All four approaches use challenging texts, or texts at the upper end of the learners' zone of proximal development, thus providing learners with access to a broader range of vocabulary and concepts than would be the case if they read only instructional level texts. All four also provided highly effective procedures for either whole-class or small-group reading instruction. The goal of this summary is to provide readers with effective approaches for classroom instruction.